Polymorphism of MTHFR 1298A>C in relation to adverse pregnancy outcomes in Chinese populations1. Issue 5 (22nd March 2019) - Mo, Hui; Rao, Meng; Wang, Gang; Long, Yan‐Xi; Wang, Hua‐Wei; Tang, Li
Abstract: Background: Adverse pregnancy outcomes (APOs) are involved in a series of abnormal pregnancies like embryo growth arrest, spontaneous abortion, premature birth, stillbirth, fetal malformation, birth defects and other pathological pregnancy, and childbirth complications. Polymorphism of methylenetetrahydrofolate reductase gene ( MTHFR, 607093) is one of the main genetic causes of APO. However, there is still debate on whether MTHFR 1298A>C, rs1801131, polymorphism is related to APO. For the lack of extensive research in the Chinese population at present, the study aim to investigate the relationship between MTHFR 1298A>C polymorphism with APO through a large number of data. Methods: A total of 241 samples from patients with APO and 117 healthy controls in Yunnan province were used for MTHFR gene polymorphism analysis, with double fluorescence quantitative polymerase chain reaction (PCR). In consideration of the low frequency of MTHFR 1298C/C genotype, which might affect the statistic results, further datasets of MTHFR 1298A>C polymorphism were collected from literature and analyzed. Results: No statistical difference was detected in the frequency of MTHFR 1298A>C polymorphism between two groups in Yunnan. Our data showed that the frequency of MTHFR 1298A/A genotype had the decreasing tendency among Chinese population from northern to southern, as well as eastern to western of China. The frequency of MTHFR 1298A/C and 1298C/C genotypes had the adverse tendency. The frequency of MTHFR 1298C/C genotype was significantly different between two groups in Chinese populations. The significant difference was also observed in the frequency of MTHFR 1298C/C polymorphism between two groups from central China and southern China. Conclusion: In summary, our data showed that MTHFR 1298C/C genotype was one of the important genetic factors of APO in China. Abstract : Polymorphisms of methylenetetrahydrofolate reductase ( MTHFR ) gene are one of the main genetic causes of adverse pregnancy outcomes (APOs). However, there is still debate on whether MTHFR 1298A>C Polymorphisms was related to APO. For the lack of extensive research in the Chinese population at present, the study aims to investigate the relationship between MTHFR 1298A>C Polymorphisms with APO through a large number of data.